Optical Emission Spectroscopy as an Online Analysis Method in Industrial Electric Arc Furnaces. Issue 11 (27th April 2020) - Pauna, Henri; Aula, Matti; Seehausen, Jonas; Klung, Jens-Sebastian; Huttula, Marko; Fabritius, Timo
Abstract : The development of online analysis methods for industrial electric arc furnaces (EAFs) has been a major research topic in recent years. Process control becomes even more important in the future due to the increase in both the usage of recycled metal as charge material and the metal recycling rate. For the industry to keep up with the pace, reliable chemical analysis of the slag together with online information about the furnace operation status is essential. Herein, optical emission spectroscopy is used to obtain the information about the electric arc together with radiative properties and surface temperature of the molten bath in an industrial EAF. The arc is visible for high alloyed steel grades within 5–30 min before tapping and the arc spectra are dominated by the optical emissions from the slag components. The plasma properties of the electric arc are determined with emission lines from atomic chromium, iron, and calcium. The time evolution of the spectra for high alloyed and carbon steel grades are compared with each other to provide a better understanding of the differences in the spectra between these two steel grades. Abstract : The applicability of optical emission spectroscopy as an online analysis tool for industrial electric arc furnaces is studied. This research focuses on spectrum intensity distribution, estimate of molten bath surface temperature, and plasma analysis of the electric arc spectra. The results for high alloyed and carbon steel grades are compared with each other.